1997
DOI: 10.1164/ajrccm.155.5.9154886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurokinin depletion on airway inflammation induced by chronic antigen exposure.

Abstract: We assessed the effects of neurokinin (tachykinin) depletion by capsaicin (CAP) treatment on airway inflammation induced by repeated ovalbumin (OA) aerosol exposures (twice a week for 4 wk) in guinea pigs. The animals were then anesthetized, tracheostomized, mechanically ventilated and challenged with ovalbumin aerosol. Maximal values of respiratory system resistance and elastance after antigen challenge were significantly lower in capsaicin-treated guinea pigs than in intact animals (p < 0.001). Morphometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
2
18

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(127 citation statements)
references
References 0 publications
7
100
2
18
Order By: Relevance
“…In the same animal model, Prado et al (28) have previously demonstrated that the inhibition of NO by chronic L-NAME treatment amplified the extracellular collagen airway remodeling. The variability in the response observed concerning collagen deposition in airways and lung tissue of this animal model may be related to the higher activity of arginase I and II in the peribronchial connective tissue (31), as well as the intensity of the inflammatory response that was greater in airways compared with that in the lung tissue (28,41).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the same animal model, Prado et al (28) have previously demonstrated that the inhibition of NO by chronic L-NAME treatment amplified the extracellular collagen airway remodeling. The variability in the response observed concerning collagen deposition in airways and lung tissue of this animal model may be related to the higher activity of arginase I and II in the peribronchial connective tissue (31), as well as the intensity of the inflammatory response that was greater in airways compared with that in the lung tissue (28,41).…”
Section: Discussionmentioning
confidence: 89%
“…Lung tissue strips were fixed at Ϫ70°C by immersion in Carnoy's fixative [solution of ethanol-chloroform-acetic acid (60:30:10)]. After 24 h, the lungs were kept at Ϫ20°C, and the concentration of ethanol was progressively increased to reach that of absolute ethanol (41). To assure the homogeneity of the strip samples used, slices were cut (5 m thick), stained with hematoxylin-eosin, and analyzed through an integrating eyepiece with a coherent system made of a 100-point grid consisting of 50 lines of known length The guinea pigs were submitted to 7 inhalations (2x/wk during 4 wk) with aerosols of normal saline or ovalbumin solution with increasing doses of antigen.…”
Section: Methodsmentioning
confidence: 99%
“…The results were expressed as cells per square millimeter (27,61,62). The perivascular edema index was established as the number of points hitting an edema area divided by the number of intercepts (lines of ocular grid) that crossed the arterial adventitia (53). The arterial muscle thickness index was assessed as the number of points hitting muscle areas divided by the number of intercepts that crossed the external limit of the muscular wall.…”
Section: Methodsmentioning
confidence: 99%
“…Modelos experimentais com múltiplas exposições a antígenos são provavelmente muito relevantes para o estudo da fisiopatologia da asma humana (Kips et al, 1992;Tibério et al, 1997). A exposição crônica de cobaias à ovoalbumina (OVA) determina um aumento da resistência e elastância do sistema respiratório (Rrs e Ers) após uma broncoprovocação aguda, além de hiperresponsividade brônquica.…”
Section: Modelos Experimentaisunclassified
“…Estas alterações parecem decorrer da contração da musculatura lisa brônquica, formação de edema peribrônquico e do aparecimento de um processo inflamatório ao redor das vias aéreas caracterizado predominantemente pela presença de eosinófilos ativados (EPO+) e linfócitos T CD3+/CD4+. Neste modelo animal encontramos resposta mecânica e inflamatória tissular, aumento do NO exalado e alterações do parênquima distal, semelhante à observada na asma humana (Tibério et al, 1997;Prado et al, 2006;Angeli et al, 2008;Nakashima et al, 2008).…”
Section: Modelos Experimentaisunclassified